The Scholarly Rewards and Tragic Irony of 3D Models in Virtual Heritage Discourse - Rahaman, Hafizur; Champion, Erik (2019)
To validate the hypothesis that a virtual heritage papers are reliant on providing scholarly argumentation based on 3D models, and convenient access is provided to these models where relevant, this study reviewed 264 articles form the last three available proceedings of major digital heritage events and conferences (14 in total). The findings revealed this was not the case, few contain references to accessible 3D models. We discuss why this may be so, and we outline recommendations for ensuring that virtual heritage 3D models can be preserved and accessed.